2016
DOI: 10.1038/srep37447
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis of Salmonella Typhimurium-infected macrophages was suppressed and elimination of intracellular bacteria from macrophages was promoted by blocking QseC

Abstract: QseC is a membrane-bound histidine sensor kinase found in Gram-negative pathogens and is involved in the regulation of bacterial virulence. LED209, a QseC-specific inhibitor, significantly inhibits the virulence of several pathogens and partially protects infected mice from death by blocking QseC. However, the mechanism of its antibacterial effects remains unclear. In this experiment, a Salmonella Typhimurium (S. Typhimurium) and macrophage co-culture system was utilized to investigate possible mechanisms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, it should be noted that given the lethality of this model, it is difficult to observe faster clearance of intestinal infection that we observed with CR, the latter of which represents a natural infection model. QseC regulates the expression of SPI-1 and SPI-2 genes (Bearson and Bearson, 2008;Moreira et al, 2010;Moreira and Sperandio, 2012;Li et al, 2016); hence, it is likely that 2-AG exerts its effects in Salmonella through QseC. Moreover, because QseC regulates virulence in other pathogens (Rasko et al, 2008;Kostakioti et al, 2009;Hadjifrangiskou et al, 2011;Curtis et al, 2014;Halang et al, 2015), it will be interesting to investigate whether 2-AG also inhibits their virulence, particularly in extraintestinal sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that given the lethality of this model, it is difficult to observe faster clearance of intestinal infection that we observed with CR, the latter of which represents a natural infection model. QseC regulates the expression of SPI-1 and SPI-2 genes (Bearson and Bearson, 2008;Moreira et al, 2010;Moreira and Sperandio, 2012;Li et al, 2016); hence, it is likely that 2-AG exerts its effects in Salmonella through QseC. Moreover, because QseC regulates virulence in other pathogens (Rasko et al, 2008;Kostakioti et al, 2009;Hadjifrangiskou et al, 2011;Curtis et al, 2014;Halang et al, 2015), it will be interesting to investigate whether 2-AG also inhibits their virulence, particularly in extraintestinal sites of infection.…”
Section: Discussionmentioning
confidence: 99%
“…with 5 mg DA/kg of body weight dissolved in 200 µl PBS or an equal volume of PBS every 12 h and sacrificed after 72 h of infection ( 52 ). The mice that received LED209 (Cayman Chemical, MI, USA) were treated orally with 20 mg/kg LED209 dissolved in 300 µl of a solution containing 19.1% dimethyl sulfoxide (DMSO; Roth), 23% PEG 400 (Sigma-Aldrich), and 55.9% sodium bicarbonate (pH 9) and 2% Tween 80 (Sigma-Aldrich) 3 h before and 3 h after infection ( 53 ).…”
Section: Methodsmentioning
confidence: 99%
“…The result showed that control +St recorded statistically high level of IFN-γ and low in the level of IL-10, this indicates that bacterial infection of tissue and phagocytic cells stimulated the cellular immune response, which contributed to an increased in the level of IFN-γ concentration as an actual result of the inflammatory response to eliminate these bacteria within the infected cells (34). Martins et al (35) found that dosed mice with S.typhimurium bacteria contributed to increased the level of pro-inflammatory cytokines, due to the activation of MAPKS and NF-KB.…”
Section: Fig (6) Level Of Interferon-γ In Groups After 8 Days Of Infmentioning
confidence: 90%